MSME Marketing Strategy in South Tangerang City During the Covid-19 Pandemic - Syamruddin Syamruddin; Gatot Kusjono (Jurnal Mandiri : Ilmu Pengetahuan, Seni, dan Teknologi, 2023)
This study aims to determine the development and marketing strategy of MSMEs in South Tangerang City during the Covid-19 Pandemic. This study uses a qualitative method. Data collection techniques consist of observation, interviews, and document analysis. Collecting data using observation techniques, interviews and documentation. Data validity is obtained through the degree of trust, transferability, dependability, and certainty. Data analysis techniques include data reduction, data exposure, and data conclusion and verification. The results of the study show that the number of MSMEs in South Tangerang City in 2022 will be 90,128. The marketing strategy carried out by MSMEs in South Tangerang City during the Covid-19 Pandemic was grouped into four aspects, namely product, price, promotion, and distribution/place. From the product aspect, in addition to offering new products, innovations are also made to existing products to make them more attractive to consumers. From the price aspect, many MSME managers make adjustments to prices. From the promotion aspect, in addition to giving discounts, promotions are carried out through word of mouth, MSME community networking, and online. From the aspect of distribution/place, the system for distributing and selling products is more limited, where MSME managers use more facilities through the online system.